2013
DOI: 10.12927/hcpol.2013.23177
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Practice Facilitation Programs in Canada: Current Perspectives and Future Directions

Abstract: Practice facilitation has proven to be effective in improving the quality of primary care. A practice facilitator is a health professional, usually external to the practice, who regularly visits the practice to provide support in change management that targets improvements in the delivery of care. Our environmental scan shows that several initiatives across Canada utilize practice facilitation as a quality improvement method; however, many are conducted in isolation as there is a lack of coordinated effort, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Such "facilitation networks" have been promoted by organizations such as the Agency for Healthcare Research and Quality to promote practice facilitation networks for improving the uptake and adoption of new knowledge in the form of evidence into primary care practice (Knox et al, 2011). It is within the role and remit of expert facilitators to establish such networks both to promote the uptake of evidence into practice (Baskerville et al, 2012;Liddy et al, 2013) and using facilitation methods to promote longerterm sustainably (Hogg, Lemelin, Moroz, Sots, & Russell, 2008).…”
Section: Facilitation Rolesmentioning
confidence: 99%
“…Such "facilitation networks" have been promoted by organizations such as the Agency for Healthcare Research and Quality to promote practice facilitation networks for improving the uptake and adoption of new knowledge in the form of evidence into primary care practice (Knox et al, 2011). It is within the role and remit of expert facilitators to establish such networks both to promote the uptake of evidence into practice (Baskerville et al, 2012;Liddy et al, 2013) and using facilitation methods to promote longerterm sustainably (Hogg, Lemelin, Moroz, Sots, & Russell, 2008).…”
Section: Facilitation Rolesmentioning
confidence: 99%
“…In Canada one of the first documented primary healthcare facilitation studies was conducted in 1997 in Ontario by Lemelin et al, who reported substantial improvement in the delivery of preventive services in the study arm supported by a practice facilitator [ 15 ]. However, only recently has the practice facilitator role been used in QI initiative programs in Canada [ 6 , 16 ], and it is still used infrequently [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Practice facilitators, also known as practice coaches or QI coaches, work closely with practices to identify areas of improvement, set improvement goals, provide tools, and facilitate QI activities and practice redesign in primary healthcare settings [ 17 ]. They are described as healthcare professionals who assist practice staff to assess care processes, plan implementation measures and improve strategies for illness prevention [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We believe this is an important area for future development to build capacity for improvement within primary care and enhance sustainability over the longer term. Practice-based facilitation is an area of growing interest and activity [ 21 , 22 ] and one that clearly involves a substantive investment in terms of people, time and resources. There are many questions still to be answered to better understand the appropriate balance between investment costs and benefits realization, for example: who should take on the facilitator role?…”
Section: Lessons Learnedmentioning
confidence: 99%